2004
DOI: 10.1108/10748120410540472
|View full text |Cite
|
Sign up to set email alerts
|

Visual literacy and learning: finding some online territories for the slow learner

Abstract: This paper is an attempt at uncovering some online practices that it is proposed utilise the age‐old lineages of the visual comic and cartoon, which can help one better understand how to create and learn through interaction enabling technologies such as those available today. As a secondary theme the paper looks at the potential for new media practices (using the label to cover a range of disciplines from design to fine arts in the digital realm) to encourage a different type of educational dialogue between st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…For students with dyslexia it may potentially be beneficial to present an alternative “pictorial” representation of a concept or process (where this is possible) alongside a standard textual description in order to potentially assist in supporting reading difficulties. However, as Leishman (2004) commented the issue of visualising and developing an interesting animated on‐screen display is a substantial task.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For students with dyslexia it may potentially be beneficial to present an alternative “pictorial” representation of a concept or process (where this is possible) alongside a standard textual description in order to potentially assist in supporting reading difficulties. However, as Leishman (2004) commented the issue of visualising and developing an interesting animated on‐screen display is a substantial task.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is in line with one of virtues of digital media that "such individuals should be regarded as unique set of problems (and strengths) and as such no one education model or indeed one set of materials can cover all". Based on the above argument, [29] carried out a study to find online territories for the slow learner. She concluded that elements in digital storytelling can be utilized to win the slow learners situation.…”
Section: Concept Of Digital Storytelling In Learning By Doingmentioning
confidence: 99%
“…For example, Wood (2003) showed that teachers can help students to use their perspectives as an important source of evidence for improving student achievement. Leishman (2004) used new techniques drawing on electronic media. He tried uncovering some online practices that encouraged a different type of educational dialogue between slow learners and teacher, a dialogue which could be useful in developing student confidence.…”
Section: Introductionmentioning
confidence: 99%